Determinan Keputusan Pembelian Produk Makanan Impor - Rifky Chalik Nabawi; Khairil Umuri; Syahriyal Syahriyal; Eka Nurlina (Universitas Nusantara PGRI Kediri, 2024)
The decision to purchase a product is basically influenced by many factors. This research aims to analyze the factors that influence the purchasing decisions of imported food products among students in Banda Aceh City. This type of research is quantitative through an associative approach. Samples were collected using nonprobability sampling techniques with a purposive sampling approach. The collected data was analyzed through multiple linear regression. The results of the research show that the halal label has no effect on students' purchasing decisions about imported food products in the city of Banda Aceh. Meanwhile, promotion, price and religiosity each influence the purchasing decisions of imported food products among students in Banda Aceh City. The implications of the research are that providers of imported food products must pay attention to halal labels, so that the food products sold do not harm consumers, especially students in the city of Banda Aceh.